ANALISIS INTERAKSIONISME SIMBOLIK TERHADAP PENYIMPANGAN PERILAKU SISWA (Kajian Sosiologi Pendidikan Terhadap Pelanggaran Tata Tertib Siswa Di SMA Negeri 9 Manado) - Tamunu, Vico Risky; Waani, Fonny J.; Tumengkol, Selvie M. (HOLISTIK, Journal Of Social and Culture, 2018)
Education is a process transformation the attitudes and behavior a person or group to mature, form and training a person or group for the better. Education also is the process of learning and hereditary of cultural values owned a community groups.Formal education is basically a school that created the state to teaching and learning students and planting values to form each student. Most schools have different procedures in order to set of every student to the learning process so that education can work well organized.Behavior or human actions basically cannot be released from the thought process. Because of the process of think that determines the actions performed by human beings. The thought process is a excess owned by human being than the other creatures. By thinking, man assess, to analyse and consider the actions he should be obeyed.A description of conduct of students SMA Negeri 9 Manado often happens in the act of playing truant; such as schools, come late, smoking, and fighting among fellow friend. In a preventive manner can do is increase the formation of; moral, character education, and maximize the process teaching quality and it is fun for the students, good advice and exemplary through every teacher.Â Keywords: school, behavior, character